Gypsum Content Horizontal and Vertical Distribution of An-Najaf and Al-Kufa Cities’ Soil by Using GIS - Al-MAMOORI, Sohaib Kareem (Basrah Journal for Engineering Sciences, 2017)
An-Najaf Province is one of the most important cities in Iraq and is experiencing rapid population growth and continuous expansion of infrastructure, including residential buildings, hotels, bridges, and commercial centers. This study aims to establish a spatial database of gypsum content in soils across An-Najaf Province, including Najaf city center and Al-Kufa city, to support safe geotechnical design. A total of 464 boreholes and in situ test records were analyzed using Geographic Information System (GIS) techniques to assess the spatial variability of gypsum content. The adopted methodology comprised four main stages: data collection, georeferencing of geotechnical data, application of interpolation methods, and map generation. Nine geotechnical distribution maps were produced for depths of 0, 2, 4, 6, 8, 10, 12, 14, 16, and 35 m. Results indicated that the 0–4 m depth layer is predominantly moderately gypsiferous, with gypsum content ranging between 10–25%. The 4–8 m depth layer is mainly slightly gypsiferous, with values between 3–10%, while deeper layers from 8 to 35 m are very slightly gypsiferous, with contents ranging from 0.3–3%. These findings show that the near-surface layers (0–4 m) exceed the allowable gypsum content limit of 10%, which may pose potential risks to construction stability, particularly in combination with the high groundwater levels in the Najaf region.